Fiscal Spending Multiplier in Selected European Union Countries - Величков, Николай (Научни трудове, 2021)
This paper estimates the fiscal spending multiplier in Bulgaria, Poland, Romania, Estonia, Denmark, Germany, Greece, and Italy for the 2000-2018 period. It is calculated by algebraically transforming the traditional Keynesian multiplier formula. In addition, the formula is subjected to further modification to take into account the impact of various structural and conjunctural factors, such as business cycle, trade openness, exchange rate regime, and fiscal sustainability, which all have an impact on the multiplier effect.